Morphological and molecular changes following neoadjuvant endocrine therapy of oestrogen receptor‐positive breast cancer: implications for clinical practice. Issue 1 (3rd May 2021) - Badr, Nahla M; Spooner, David; Steven, Jane; Stevens, Andrea; Shaaban, Abeer M
Abstract : Aims: Neoadjuvant endocrine therapy (NAET) is used in the management of oestrogen receptor (ER)‐positive breast cancer. The optimal method for histological assessment of response and the effect of NAET on the tumour morphology, grade and molecular profile remain unclear. The aim of this study is to investigate the NAET effect on tumour type, grade and molecular profile by analysing a well‐characterised cohort of breast cancer samples in a single large UK tertiary referral centre, and to provide guidance on the pathological assessment of those lesions to inform adjuvant management and prognosis. Methods and results: A single large‐institution cohort of 132 patients who received NAET over a 13‐year period was identified. Comprehensive clinical, histopathological and follow‐up data were collected. A detailed histological review of a subset with residual post‐treatment carcinoma was undertaken. Two carcinomas (both of the lobular type) achieved complete pathological response. Central scarring was seen in 49.3% of tumours post‐treatment. Significant changes in tumour type (41.6%), tumour grade (downgrading in one‐third of tumours), and progesterone receptor (PR) expression (22.3%), with a switch to PR‐negative status in 17.6% of cases, were observed. The last of these was associated with an absence of tumour‐infiltrating lymphocytes ( P = 0.005). Ten per cent of cases showed a change in HER2 expression ( P = 0.002). The median patient survival was 60 months, and downgrading of tumours was associated with better overall survival ( P = 0.05). Conclusions: We propose a histological method for assessment of residual carcinoma following NAET, and recommend repeat ER/PR/HER2 testing to inform management and prognosis. Abstract :